Partial blindness to submicron topography in NF1 haploinsufficient cultured fibroblasts indicates a new function of neurofibromin in regulation of mechanosensoric - Kaufmann, Dietrich; Spatz, Joachim P. (Molecular syndromology, 2012)
Cells sense physical properties of their extracellular environment and translate them into biochemical signals. In this study, cell responses to surfaces with submicron topographies were investigated in cultured human NF1 haploinsufficient fibroblasts. Age-matched fibroblasts from 8 patients with neurofibromatosis type 1 (NF1+/−) and 9 controls (NF1+/+) were cultured on surfaces with grooves of 200 nm height and lateral distance of 2 μm. As cellular response indicator, the mean cell orientation along microstructured grooves was systematically examined. The tested NF1 haploinsufficient fibroblasts were significantly less affected by the topography than those from healthy donors. Incubation of the NF1+/− fibroblasts with the farnesyltransferase inhibitor FTI-277 and other inhibitors of the neurofibromin pathway ameliorates significantly the cell orientation. These data indicate that NF1 haploinsufficiency results in an altered response to specific surface topography in fibroblasts. We suggest a new function of neurofibromin in the sensoric mechanism to topographies and a partial mechanosensoric blindness by NF1 haploinsufficiency.